Novel Presentation of Pediatric Complex Regional Pain Syndrome with Concurrent Chromhidrosis: A Case Report. Issue 3 (July 2021) - Wallace, Calum; Coulter, John L.; Sebes, Nick; Seeley, Mark
Abstract : Case: An 11-year-old female patient presented to our clinic with a low-grade lateral ankle sprain that was subsequently treated with a lace-up ankle brace. On the reintroduction of weight bearing, the patient developed recurrent ankle pain and symptoms consistent with complex regional pain syndrome (CRPS) Type 1. On physical examination, the patient was found to have a concurrent chromhidrosis in the injured area, which is a novel presentation of CRPS. Conclusion: Patients with CRPS found to have superficial skin discoloration should be evaluated further to investigate for chromhidrosis. Early diagnosis can improve the treatment of CRPS and allow for appropriate management of varying manifestations, such as chromhidrosis.